Green synthesis of cyclohexanone to adipic acid over Fe-W oxides incorporated mesoporous carbon support - Mekala, Siva Prasad; Prabu, Marimuthu; Gawali, Sheetal Datta; Gopakumar, Karthik; Gogoi, Pranjal; Bhatkar, Akash Ravindra; Mohapatra, Gourab; Unnikrishanan, Eeswar; Raja, Thirumalaiswamy (Catalysis Communications, 2022)
We have prepared iron and tungsten oxides incorporated mesoporous carbon (MC) catalysts using a simple hydrothermal methodology with different carbon sources, and the catalytic performance was investigated for cyclohexanone oxidation. An adequate amount of metal oxide loading has displayed a key role in the selective catalyst for adipic acid (AA) synthesis. The MC catalyst has shown its prime activity under the influence of redox properties of W5+/W6+ and Fe2+/Fe3+ as promoters. The 10%Fe 90%W-MC fructose as a carbon source catalyst has provided its best selectivity of 87% for AA at 120 ?C.
Keywords: Adipic Acid; Liquid phase oxidation; mesoporous carbon; Redox center

Microwave-assisted selective N-alkylation of aniline over molybdenum supported catalyst - Bhatkar, Akash; Mane, Samruddhi; Mekala, Siva Prasad; Gogoi, Pranjal; Mohapatra, Gourab; Ramakrishnan, Archana; Marimuthu, Prabu; Thirumalaiswamy, Raja (Catalysis Communications, 2022)
Selective N-alkylation of aniline is a tough and challenging reaction due to over alkylation, therefore, catalyst with specific characteristics is needed to accomplish such transformations. In this work, a series of catalysts with molybdenum supported on alumina are prepared and subjected to various reaction conditions, out of which 30 PMA (Phosphomolybdic acid) showed the best result due to its proper combination of acidic sites. This reaction is sustainable and environmentally friendly as it is carried out with methanol as an alkylating source in the presence of microwave radiation at low temperature. The reaction data was compared with various other reactor systems too.